The investment return puzzle on the Johannesburg Stock Exchange. Issue 3 (3rd July 2018) - Semnarayan, Pravin; Ward, Michael; Muller, Chris
ABSTRACT: Firms that invest into positive net present value projects should outperform firms that do not invest. Surprisingly, several studies on United States data have found a negative relationship between capital investment and subsequent shareholder return. There are conflicting explanations for this negative relationship. The present study also confirmed a significant negative relationship between capital investment and subsequent shareholder returns in the South African developing market conditions. Over the period from 1992 to 2017, shares on the Johannesburg Stock Exchange with lower investment rates consistently outperformed shares with higher investment rates, exhibiting similar behaviour to the US. We find that the negative investment return is significantly associated to the firm's book-to-market value consistent to the rational-based q-theory of investment with real options explanation.